Analisis Segmentation, Targeting, Dan Positioning (STP) Terhadap Pembelian Pada Restoran Mbak Daeng Abdesir - Suriansyah; M. Ikhwan Maulana; Zainal Ruma; Muhammad Ilham Wardhana Haeruddin; M. Ichwan Musa (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Segmentation, Targeting, and Positioning (STP) Analysis of Purchases at Mbak Daeng Abdesir Restaurant. Thesis Management Study Program, Faculty of Economics and Business, Makassar State University Supervised by Muhammad Ikhwan Maulana and Zainal Ruma. This study aims to determine the effect of segmentation, targeting, and positioning (STP) on purchases at Mbak Daeng Abdesir Restaurant. This research variable consists of segmentation, targeting and positioning as independent variables, purchase as the dependent variable. This type of research is quantitative associative in nature. The data collection technique was carried out by distributing questionnaires to consumers. The data analysis technique uses multiple regression with the help of SPSS software version 27. The results of this study indicate that Segmentation and Targeting have a positive and significant effect on purchases partially. Meanwhile, Positioning has no effect on purchases. However, simultaneously Segmentation, Targeting, and Positioning (STP) have a positive and significant effect on purchases at Mbak Daeng Abdesir Restaurant.